2011
DOI: 10.1159/000330811
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of Liquid-Based Cytology and Traditional Smear Cytology in Pancreatic Endoscopic Ultrasound-Guided Fine Needle Aspiration

Abstract: Objective: To compare results of liquid-based cytology (LBC) and the conventional smear method (SMEAR) when performing endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) for lesions of suspected pancreatic malignancy without an on-site cytopathologist. Study Design: Fifty-eight patients were prospectively enrolled between July and December 2009. Aspirates obtained from the first needle pass were randomized either to SMEAR or LBC. Another sample from the second needle pass was allocated to the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 47 publications
1
44
1
1
Order By: Relevance
“…LeBlanc et al [24] reported that LBC was inferior to SC for the detection of pancreatic malignancy in a study that employed an on-site cytopathologist during the EUS-FNA procedure. In addition, a prospective study found that LBC was less accurate than SC after EUS-FNA in patients with pancreatic malignancy [8]. We found that the diagnostic efficacy of LBC was relatively higher than that of SC.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…LeBlanc et al [24] reported that LBC was inferior to SC for the detection of pancreatic malignancy in a study that employed an on-site cytopathologist during the EUS-FNA procedure. In addition, a prospective study found that LBC was less accurate than SC after EUS-FNA in patients with pancreatic malignancy [8]. We found that the diagnostic efficacy of LBC was relatively higher than that of SC.…”
Section: Discussionmentioning
confidence: 61%
“…Cytological results from all methods were reported as follows: (1) definite malignancy, (2) suspicion of malignancy, (3) benign cytology, (4) inadequate for diagnosis. Patients were stratified to the “malignancy” group when their results were either (1) definite malignancy or (2) suspicion of malignancy [8].…”
Section: Methodsmentioning
confidence: 99%
“…With regard to diagnosis of pancreatic malignancy via EUS‐FNA, the superiority of LBC over CS with or without ROSE is yet to be fully established . However, several reports have shown the efficacy of EUS‐FNA with LBC .…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound-guided fine needle aspiration was performed for the large mass using 22 Gauge FNA needle (arrow) With regard to diagnosis of pancreatic malignancy via EUS-FNA, the superiority of LBC over CS with or without ROSE is yet to be fully established. 15,16 However, several reports have shown the efficacy of EUS-FNA with LBC. 8,17 Furthermore, Rossi et al also demonstrated that LBC preparation of EUS-FNA specimens can be useful even in primary pancreatic lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Onsite pathologist is probably the most important factor determining the success of EUS‐FNA result . Regarding tissue preparation, liquid‐base cytology is thought to be better than conventional smear method; however, a recent prospective study from Korea showed that the former was less accurate . Another large recent study also confirmed higher accuracy rate of conventional smear compared with ThinPrep method, at 98% versus 64%, respectively …”
Section: Role Of Eus In the Diagnosis And Evaluation Of Pancreatic Tumormentioning
confidence: 99%